Valoración de dos compuestos enzimáticos usados en el alimento balanceado para pollos broiler sobre los parámetros productivos. - Cortes Abad, Becsi Cristina; Velasco Reyes, Brithany Naomi (Machala : Universidad Técnica de Machala, 2023)
The present research was carried out at the facilities of the Technical University of Machala, province of El Oro, in a shed of the "Santa Inés" farm located in the Faculty of Agricultural Sciences, following the procedure established in the Guide of Good Poultry Practices (GPP). The objective of the essay was to evaluate two enzymatic compounds applied in a chicken smash feed formula for broiler chickens, analyzing the effects and their possible benefits in the productive parameters after the ingestion of feed with the enzymatic compounds. The work carried out was of the experimental type, where 3 treatments were used with 4 repetitions respectively, in each experimental unit 15 broilers were placed; in this way a Completely Randomized Design (CRD) was used using a total of 180 broilers of the Cobb 500 breed. The first treatment (T1) corresponded to the feed that included the enzymatic compound Huvezym PC®, in the second treatment (T2) the enzymatic compound Rovabio® MAX ADVANCE was incorporated; finally, the third treatment (T3) did not include enzymes, determined as a control treatment; it should be noted that the name used for each treatment, that is, T1, T2 and T3 were randomly distributed for each treatment. Data were collected daily, such as water consumption, feed administration, management control to provide quality of life and weekly, the accumulated feed consumption, weight obtained and the elaboration of the balance corresponding to each treatment according to the stage of life in which they were. The variables studied were: Average live weight, feed consumption, water consumption, conversion index, mortality, PEF (production efficiency factor), weight per m2 (Kg), average expenses per EU, cost per Kg of standing meat per m2, cost of standing meat per Kg, cost of standing meat per Kg, cost of standing meat per Lb. Once the treatments of each experimental unit were established, they were labeled based on the replicate and its treatment; the statistical evaluation was carried out using Statgraphics Centurión XV.I.® software, applying a single factor analysis (ANOVA), using the Tukey hsd confidence interval (95%). The results of the inclusion of enzymatic compounds in the balanced formula for broiler chickens have no effect on the variables analyzed and on the productive parameters of the broilers studied (average live weight, feed consumption, water consumption, conversion rate, productive efficiency factor, mortality, average weight per m2); on the other hand, the economic parameters (expenses per experimental unit, cost per kg of standing meat per m2, cost of standing meat per kg and cost of standing meat per lb) were not significantly affected, which indicates that the inclusion of these enzymatic compounds in the broiler chickens' feed is neither detrimental nor beneficial for poultry production.
La presente investigación se llevó a cabo en las instalaciones de la Universidad Técnica de Machala, Provincia de El Oro, en un galpón rejado de la granja "Santa Inés" ubicada en la facultad de Ciencias Agropecuarias respetando el procedimiento establecido en la Guía de Buenas Prácticas Avícolas (BPA). El objetivo del ensayo consistió en valorar dos compuestos enzimáticos aplicados en una fórmula balanceada para pollos broiler mediante el análisis de los efectos y sus posibles beneficios en los parámetros productivos tras la ingesta del alimento con los compuestos enzimáticos. El trabajo realizado fue de tipo experimental, donde se empleó 3 tratamientos con 4 réplicas respectivamente, en cada unidad experimental se ubicaron 15 pollos; de esta manera se empleó un Diseño Completamente al Azar (DCA) utilizando un total de 180 aves de engorde raza Cobb 500. El primer tratamiento (T1), correspondió al alimento que se incluyó como compuesto enzimático Huvezym PC®, en el segundo tratamiento (T2) se incorporó el compuesto enzimático Rovabio® MAX ADVANCE; finalmente, el tercer tratamiento (T3) no contó con la inclusión de enzimas, determinado como un tratamiento testigo; cabe señalar que la denominación empleada a cada tratamiento, es decir, T1, T2 y T3 fueron distribuidas para cada tratamiento de forma aleatoria. Los datos se recolectaron diariamente como el consumo del agua, la administración del alimento, control del manejo para ofrecer calidad de vida y semanalmente se registró el consumo de alimento acumulado, el peso obtenido y elaboración del balanceado correspondiente a cada tratamiento de acuerdo a la etapa de vida en la que se encontraban. Las variables que se estudiaron respectan a: Promedio de peso vivo, consumo de alimento, consumo de agua, índice de conversión, mortalidad, FEP (factor de eficiencia de producción), peso por m2 (Kg), promedio de gastos por UE, costo del Kg de carne en pie por m2, costo de carne en pie por Kg, costo de carne en pie por Lb. Una vez establecidos los tratamientos de cada unidad experimental fueron rotulados en base a la réplica y su tratamiento; la evaluación estadística se llevó a cabo utilizando el software Statgraphics Centurión XV.I.®, aplicando un análisis de un solo factor (ANOVA), utilizando el intervalo de confianza Tukey hsd (95%). Los resultados de la inclusión de compuestos enzimáticos en la fórmula balanceada para pollos broiler no tienen efecto sobre las variables analizadas y sobre los parámetros productivos de los pollos de engorde estudiados (promedio de peso vivo, el consumo de alimento, el consumo de agua, el índice de conversión, el factor de eficiencia productiva, la mortalidad, el promedio de peso por m2); por otra parte, los parámetros económicos (gastos por unidad experimental el costo del Kg de carne en pie por m2, costo de carne en pie por Kg y costo de carne en pie por Lb) tampoco se vieron significativamente afectados, esto indica que la inclusión de estos compuestos enzimáticos en el alimento balanceado de los pollos broiler no resultan perjudiciales ni beneficiosos para la producción avícola.
Keywords: COMPUESTOS ENZIMATICOS; POLLOS BROILER; ALIMENTACION; PARAMETROS PRODUCTIVOS